Psychosocial factors affecting the adherence of chronic kidney disease patients to undergo a hemodialysis program: a cross-sectional study - Rondhianto, Rondhianto; Murtaqib, Murtaqib; Yonda, Nila Nabila (Universitas Airlangga, 2024)
Introduction: This study aims to analyze the effect of psychosocial factors on hemodialysis program adherence. Methods: The study was cross-sectional, with a sample size of 90 respondents, obtained through simple random sampling. The study’s dependent variable was hemodialysis program adherence and the independent variables were knowledge, motivation, coping, depression, perceived family support and health worker support. Data were collected using a questionnaire and analyzed using multiple linear regression. Results: Most respondents adhered to the hemodialysis program (90%). The level of knowledge, motivation, coping, family support, and health worker support was in the good category (93.3%; 100%; 91.1%; 90%; 88.9%, respectively), and did not experience depression (90%). The independent variables (knowledge, motivation, coping, family support, health worker support) simultaneously significantly affected the dependent variable, namely adherence to the hemodialysis program by 94.5% (R2 = 0.945; F = 236.613; p = 0.001). Partially, the factors of knowledge, motivation, coping, family support, health workers support, and depression also had a significant effect on hemodialysis program adherence (t = 2.234, t = 5.344, t = 3.473, t = -4.190, t = 6.457, t = 4.887, t = 4.190, respectively; p = 0.001). Conclusions: The study results showed that psychosocial factors (knowledge, motivation, coping, family support, health worker support, and depression) simultaneously or partially influenced the adherence of CKD patients to undergo a hemodialysis program, with the most dominant factor affecting adherence to hemodialysis as perceived family support. Keywords: Adherence, Hemodialysis, Psychosocial